Default Effects And Follow-On Behaviour: Evidence From An Electricity Pricing Program. (12th April 2021) - Fowlie, Meredith; Wolfram, Catherine; Baylis, Patrick; Spurlock, C Anna; Todd-Blick, Annika; Cappers, Peter
Abstract: We study default effects in the context of a residential electricity-pricing program. In the large-scale randomized controlled trial we analyse, one treatment group was given the option to opt-in to time-varying pricing while another was defaulted into the program but allowed to opt-out. We provide dramatic evidence of a default effect on program participation, consistent with previous research. A novel feature of our study is that we also observe how the default manipulation impacts customers' subsequent electricity consumption. Passive consumers who did not opt-out but would not have opted in—comprising more than 70$%$ of the sample—nonetheless reduce consumption in response to higher prices. Observing of this follow-on behaviour enables us to assess competing explanations for the default effect. We draw conclusions about the likely welfare effects of defaulting customers onto time-varying pricing.